Metodologías activas en la asignatura de Lengua y Literatura - Cormillo Tipan, Erika Dayana (2023)
Nowadays, society demands a quality education, so teaching work is increasingly demanding since the teacher is in charge of ensuring the corrected development of teaching and the significant knowledge acquired by the student. In this sense, this research has as aims to apply active methodologies through demonstration classes in order to improve the teaching and learning process in the area of Language and Literature in the 5th grade of the "Simón Rodríguez" School. Regarding the project, it became evident that the methodologies applied by the teacher do not respond to the needs of the students since they provoked traditionalist learning, focusing on the memorization of the content. The applied methodology was qualitative since the educational reality was described in the didactic process; also, the observation technique allowed the collection of relevant data on the application of the active methodologies in the teaching-learning process, being the instrument of the observation guide in which information was obtained from the class. As for the results, it was the schematization of the categories obtained from the interpretations made based on the information collected from the demonstration classes in the area of Language and Literature, where the key ideas of the research were present, in addition, the intended to disseminate the results in digital magazines. In conclusion, active methodologies allow the development of abilities, skills, and attitudes directed toward meaningful learning, strengthening reading comprehension and critical thinking.